Association between intrusive negative autobiographical memories and depression: A meta‐analytic investigation. (23rd February 2018) - Mihailova, Stella; Jobson, Laura
Abstract: The study investigated several associations between depression and intrusive negative autobiographical memories. A systematic literature search identified 23 eligible studies ( N = 2, 582), which provided 59 effect sizes. Separate meta‐analyses indicated that depression was moderately, positively associated with intrusive memory frequency, memory distress, maladaptive memory appraisals, memory avoidance, and memory rumination. Intrusive memory vividness was not significantly associated with depression. There were insufficient data to examine the relationship between depression and memory vantage perspective. Between‐study heterogeneity was high for intrusive memory frequency and memory avoidance, and the percentage of females in studies significantly moderated the relationship between these variables and depression. An additional exploratory meta‐analysis (3 studies; N = 257) indicated that intrusive memories were experienced more frequently by those with posttraumatic stress disorder than those with depression. Overall, the findings suggest that intrusive memories warrant clinical attention as they may contribute to the maintenance of depressive symptomatology.